Association between thrombocyte and neutrophyl count with cutaneous manifestations in children with acute lymphocytic leukemia and acute myelocytic leukemia - Hariani, Eva; Purnama, Sri Wahyuni; Siregar, Remenda (International Journal of Research in Medical Sciences, 2019)
Background: Acute leukemia is a hematopoietic stem cell malignant disease, with abnormal proliferation of leukemic and immature cells that suppress the production of normal blood cell and extensively invade peripheral tissues organs including skin. Homeostatic abnormalities that occur in leukemia e.g. thrombocytopenia and neutropenia. Various cutaneous manifestations can be observed in leukemia but the etiology is usually unknown, because many factors are responsible for this cutaneous manifestation. The aim of the present study was to determine association between thrombocyte and neutrophyl count with cutaneous manifestations in children with Acute Lymphocytic Leukemia (ALL) and Acute Myelocytic Leukemia (AML). Methods: This is an observational analytical cross-sectional study involving 51 children with acute leukemia (ALL and AML) were hospitalized in H. Adam Malik General Hospital Medan during April – September 2018. Interview, dermatology examination and recording thrombocyte and neutrophil count were performed to the subjects. Differences between thrombocyte and neutrophyl count with cutaneous manifestations were analyzed using Mann Whitney test. Association between thrombocyte and neutrophyl count with cutaneous manifestations were analyzed using Kolmogorov Smirnov test. Results: Children with Acute Leukemia in this study most of them were girls (51.0%), age between 0 - 5years old (39.2%). There were no significant differences between thrombocyte and neutrophyl count with cutaneous manifestations in children with acute leukemia (p value 0.692 and 0.814). There was no significant association between thrombocyte and neutrophyl count with cutaneous manifestations in children with acute leukemia (p value 0.490 and 0.803). Conclusions: There is no significant association between thrombocyte and neutrophyl count with cutaneous manifestations in children with acute leukemia.